Progressive multifocal leukoencephalopathy in Finland: a cross-sectional registry study - Jussi O. T. Sipilä; Merja Soilu-Hänninen; Päivi Rautava; Ville Kytö (Springer Berlin Heidelberg, 2022)
OBJECTIVE:To investigate if progressive multifocal leucoencephalopathy (PML) incidence has increased in Finland like in the neighbouring Sweden.
METHODS: National administrative registries were searched for all PML admissions aged 16 years or more in 2004-2014 on all neurological and internal medicine wards in Finland. The mortality data of the patients was extracted from the national causes of death registry. National level data on annual predisposing drug use was obtained from the national pharmaceutical authority.
RESULTS: We identified 35 PML cases (57% male) with a peak in 2010-2011 that amounted to 49% of all cases. The annual incidence for the entire study period was 0.072/100,000 person-years (95% CI 0.050-0.10) with no temporal trend (p = 0.18). Mean age was 57 years (22-88 years) with no sex difference (p = 0.42). Neoplasms (60%), HIV infection (17%) and systemic connective tissue disorders (CTD, 14%) were the most common predisposing conditions. MS was recorded in three cases (9%). The national level use of drugs that predispose to PML increased during the study period, with the exceptions of alemtuzumab and fludarabine. Overall survival was 85% at 90 days, 79% at 1 year, and 66% at 5 years. Survival was worst in patients with malignancy and best in patients with CTD.
CONCLUSIONS: PML most often occurs in patients with malignancies and patients with HIV or CTD cover a third. PML incidence in Finland is lower than in Sweden and shows no temporal trend despite increasing use of predisposing drugs. Mortality after PML varies according to the predisposing condition.